Child misbehavior in an early childhood classroom: Montessori educators' views and practices - Kural, Elif; Ceylan, Remziye (Southeast Asia Early Childhood Journal, 2022)
Within the scope of Montessori education system, which has been widely applied in Turkey in recent years, “prepared environment”, “didactic materials” and “prepared adult” concepts have been frequently emphasized. It could be asserted that behavior management at Montessori classrooms is formed and arranged within the frame of these three basic factors. This study intends to determine the classroom management practices of Montessori educators who work in public or private preschool institutions’ three-six-year-old early childhood departments in Turkey and how they associate these practices with classroom management. The study was carried out in line with a phenomenological approach, one of the qualitative research methods, and the sample is comprised of 13 Montessori educators working in 4 different institutions located in Istanbul’s Basaksehir, Umraniye, Sancaktepe, and Sariyer districts. The data was obtained through individual face-to-face interviews and a follow-up interview by using the questions prepared by researchers. The findings were obtained by descriptive analysis. Data on the classroom management practices were collected under the theme of management of misbehaviors and 18 practices were identified under this theme. According to findings of the follow-up interview, educators associate the practices they apply for behavior management with classroom management within the frame of the prepared environment, prepared adult, and didactic materials. Future researchers can design studies to compare the practices of Montessori educators and educators working in different approaches towards misbehaviours.